2019
DOI: 10.1027/0269-8803/a000226
|View full text |Cite
|
Sign up to set email alerts
|

Negative Affect-Related Autonomic Arousal Mediates the Association Between Baroreflex Dysfunction and Insulin Resistance in Non-Diabetic Young Adults

Abstract: Abstract. Autonomic dysfunction, in particular under-regulation of heart rate (HR) by the baroreflex, is implicated in development of insulin resistance (IR). According to reactivity hypothesis, sympathetic response to stressors may be more sensitive at predicting IR than baroreceptor sensitivity (BRS), a baseline measure of baroreflex functioning. Using ecological momentary assessment (EMA) of negative affect coupled with minute-to-minute HR and heart-rate variability (HRV) monitoring, we examined whether neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Our screening results identified three different types of cardiovascular measures: blood pressure, heart rate, and heart rate variability. Blood pressure was assessed in 19 reports [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] (Table 2), heart rate in 21 studies [37-39, 42, 43, 45-47, 51, 53, 56-66] (Table 3), and heart rate variability in 12 studies [56,58,59,62,64,65,[67][68][69][70][71][72] (Table 4). Specifically, BP was measured as systolic (SBP) or diastolic (DBP) blood pressure, mean arterial pressure (MAP), or pulse pressure (PP).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our screening results identified three different types of cardiovascular measures: blood pressure, heart rate, and heart rate variability. Blood pressure was assessed in 19 reports [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] (Table 2), heart rate in 21 studies [37-39, 42, 43, 45-47, 51, 53, 56-66] (Table 3), and heart rate variability in 12 studies [56,58,59,62,64,65,[67][68][69][70][71][72] (Table 4). Specifically, BP was measured as systolic (SBP) or diastolic (DBP) blood pressure, mean arterial pressure (MAP), or pulse pressure (PP).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Ten different devices were used to measure blood pressure, with the most common device being the Spacelabs model 90207 (N = 5; 31% for SBP and 22% for DBP) [39,40,42,50,53]. Fifteen different devices were used to measure heart rate, with the most common devices being a Holter device in four (19%) studies [56,58,62,74], Spacelabs model 90207 in three studies [39,42,53], and VU-AMS in two (10%) studies [64,65]. For heart rate variability, seven different devices were identified and the most used devices were either a Holter monitor [56,58,62] or a Movisens EcqMove [70][71][72] device in three studies each (25%).…”
Section: Plos Onementioning
confidence: 99%
“…A similar pattern is observed for HRV, but with more variability: it is negatively associated with general negative affect (Bacon et al, 2004;Pieper et al, 2007;Conrad et al, 2008;Kimhy et al, 2010), and with negative affect with high arousal (Bacon et al, 2004;Pieper et al, 2007). When arousal is low, HRV has been negatively (Simon et al, 2021, Liu et al, 2022, positively (Kim et al, 2021), or not (Dennis et al, 2018;Määttänen et al, 2021) associated with negative affect. The overall reduction in HRV is also seen during general positive affect (Bacon et al, 2004;Conrad et al, 2008;Kennedy et al, 2015;Simon et al, 2021) and positive affect paired to high arousal (Gerteis & Schwerdtfeger, 2016).…”
Section: Introductionmentioning
confidence: 56%
“…Studies show that HR was positively associated with negative affect when arousal is high (Pieper et al, 2007;Pollard et al, 2007;Lumley et al, 2014;Kennedy et al, 2015;Ensari et al, 2020;Gordon & Mendes, 2021;Kim et al, 2021;Simon et al, 2021) or low (Kim et al, 2021;Simon et al, 2021;Liu et al, 2022). For general (i.e., not taking arousal levels into account) negative affect mixed results are found, with both positive (Pieper et al, 2007;Ilies et al, 2010), negative (Sloan et al, 1994), and non-significant relationships (Kamarck et al, 1998;Kimhy et al, 2010;Dennis et al, 2018;Määttänen et al, 2021) identified. Furthermore, HR is also positively associated with general positive affect (Ensari et al, 2020;Määttänen et al, 2021;Simon et al, 2021) and with positive affective states characterized by high arousal (Gordon & Mendes, 2021).…”
Section: Introductionmentioning
confidence: 99%